PELVIC FLOOR MUSCLE TRAINING VERSUS NO TREATMENT FOR URINARY INCONTINENCE IN WOMEN - Ndreu, Vjollca; Kamberi, Fatjona; Sinaj, Enkeleda; Sula, Anila (European Scientific Journal, ESJ, 2015)
Pelvic floor muscle training is the most commonly used physical therapy treatment for women with urinary incontinence (UI). According to the World Health Organization bladder problems affect more than 200milion people worldwide. Urinary incontinence is a disorder that affects women far more frequently than men; 85% of people suffering from urinary incontinence are women. According to existing studies and literature few women go to consult a therapist who specializes in urinary incontinence in our country. Talking about UI, it is a taboo for most women, especially for women living in small cities or rural area. The purpose of the study was to determine the effects of pelvic floor muscle training for women with urinary incontinence in comparison to no treatment. This is a randomized control trial and to gather information was used a questionnaire( ICIQ-SF), and personal contact with patients. The patients were randomly allocated into two groups, the control group and the experimental group. The experimental group practiced PFME at home, the control group didn’t practice PFME at home. The study indicates that physiotherapy has a key role in the conservative treatment of UI and is less costly than other methods of treatment. PFME gives good results in controlling involuntary loss of urine. This treatment isn’t very recognized in Albania. One of the best ways to introduce this method will be from the family doctors and from maternity staff who treats the most effected patients, future mothers.